THE EXPERIENCE OF SELECTED TYPHOON HAIYAN SURVIVORS ON CO-OPERATIVE FORMATION AS PART OF THEIR REBUILDING AND RECOVERY STRATEGY (CASE STUDY APPROACH) - Corpuz, Crispina R (PEOPLE: International Journal of Social Sciences, 2019)
This paper was initiated as an offshoot to help selected Typhoon Haiyan survivors and to serve as a model to other calamity survivors who would like to help themselves after the devastation. It considered the experience of selected Typhoon Haiyan survivors on the co-operative formation. It also ascertained how cooperative formation could help create jobs as rebuilding strategy to help the survivors of calamities. The study used the case study methodology to develop a theory on cooperative formation for the survivors of calamities and to evaluate the cooperative entrepreneurship livelihood program as an intervention. Findings show that formation of coops could create jobs and contribute to helping the survivors to escape from poverty. The cooperative formation mobilized the selected typhoon survivors to be together and look for solutions that could help them rebuild what they had lost during the calamity. These outcomes support the literature review showcasing how cooperative formation is well suited to ordinary people, including survivors of calamities who do not have enough capital to put up their own business. It would be to the advantage of survivors of different calamities to have similar studies that would support the identified research outcomes for easier replication and modeling.